Horizontal and vertical agreements: Differences between the European Union and the United States - Harrington Joseph E. Jr. (Anali Pravnog Fakulteta u Beogradu)
This article compares the European Union and the United States with respect to competition law and enforcement practices as it pertains to agreements among competitors in a market (horizontal) and agreements among firms in a supply chain (vertical). Regarding horizontal agreements, the primary difference in the law is the ability of the competition authority to bring a criminal case in the U.S. and a more subtle difference is the presence of concerted practices in the EU. Enforcement differs in the far more active role of private litigation in the U.S. The differences are greater when one turns to vertical agreements. Though the EU provides safe harbors for vertical agreements, something which is absent in the U.S., it is abundantly clear that the U.S.is more lenient in the law and in enforcement. Also provided is a discussion of some recent departures between the U.S. and EU.